Sensualitas Media Sosial di Era Globalisasi (Kajian Sosiologi Media McLuhan sebagai Analisis Media Masa Kini) - Zahid, A (Sociology Department Of Syiah Kuala University, 2019)
Historically, McLuhan stated that electronic dependence in the age of globalization has made humans in a great imagination called